Impact of non-neuronal cells in Alzheimer’s disease from a single-nucleus profiling perspective - Vu, Tra-My; Hervé, Vincent; Ulfat, Anosha Kiran; Lamontagne-Kam, Daniel; Brouillette, Jonathan (Frontiers in Cellular Neuroscience, 2023)
The role of non-neuronal cells has been relatively overlooked in Alzheimer’s disease (AD) neuropathogenesis compared to neuronal cells since the first characterization of the disease. Genome wide-association studies (GWAS) performed in the last few decades have greatly contributed to highlighting the critical impact of non-neuronal cells in AD by uncovering major genetic risk factors that are found largely in these cell types. The recent development of single cell or single nucleus technologies has revolutionized the way we interrogate the transcriptomic and epigenetic profiles of neurons, microglia, astrocytes, oligodendrocytes, pericytes, and endothelial cells simultaneously in the same sample and in an individual manner. Here, we review the latest advances in single-cell/nucleus RNA sequencing and Assay for Transposase-Accessible Chromatin (ATAC) sequencing to more accurately understand the function of non-neuronal cells in AD. We conclude by giving an overview of what still needs to be achieved to better appreciate the interconnected roles of each cell type in the context of AD.